English Equivalents for Indonesian Relative Pronoun ‘yang’: A Comparative Study - Afrianto Afrianto (Kantor Bahasa Lampung, 2022)
This research discusses Indonesian relative clauses compared to its translation of English in the short story Clara atawa Wanita yang Diperkosa. The aim of this research is to configure and describe the differences and similarities of relative clauses in Indonesian and English. In this research, the researchers applied the qualitative method since the researchers gave detailed descriptions and explanations of the lingual phenomena from existing documents exploratively. This research found that the patterns of relative clauses in Indonesian and English perform similarities and differences. A similar pattern found is RP-V-O/Adjunct, while the difference is caused by structural shiftings happening in translating process. Furthermore, there are three equivalents for the relative pronoun ‘yang’, they are who, which, and that. Moreover, ‘yang’ is not always translated when the translation is constructed in a deep structure construction. Furthermore, this research presents the alternative ways to choose the appropriate English relative pronoun to translate the Indonesian relative pronoun.